author Kyle Spaans Mon, 11 May 2009 04:02:16 +0000 (00:02 -0400) committer Kyle Spaans Mon, 11 May 2009 04:02:16 +0000 (00:02 -0400)
 lec02-0506.tex patch | blob | history lec03-0508.tex patch | blob | history

index 7020919..1c03e8b 100644 (file)
@@ -13,24 +13,48 @@ hyperboloid (one sheet''), cone, hyperboloid (two sheets''), up/down
elliptic paraboloid. To visualize these, look up Interactive Gallery of

-Consider a function $\frac{x^2}{a^2} + \frac{y^2}{b^2} + l \frac{z^2}{c^2} = k$
+\paragraph*{Example 1}
+Consider a function
+$\displaystyle \frac{x^2}{a^2} + \frac{y^2}{b^2} + l \frac{z^2}{c^2} = k$
Let
$z = k \Rightarrow \frac{x^2}{a^2} + \frac{y^2}{b^2} = l - \frac{k^2}{c^2}$
from which we expect to want positive values on the right-hand-side,
-$\|k\| \le c$.
+$\|k\| \le c$. This gives us an ellipse, so the level curves'' will be in
+the form of an ellipse. And if we turn the crank on $x = k$ and $y = k$ the
+picture the z-axis as well to get full
+3D, we can something that's an ellipse from all angles.
+$\frac{x^2}{a^2(1 - \frac{k^2}{c^})} + \frac{y^2}{b^2(1 - \frac{k^2}{c^})}$

-Blah blah, a bunch of drawing stuff...
+\paragraph*{Example 2}
+$y = x^2$
+On a plane, this is a parapola. In 3D we assume this parapola $\forall z$,
+giving us a parabolic surface. Think of a folded piece of paper.
+
+\paragraph*{Example 3 - Hyperbolic Paraboloid (saddle surface)}
+$z = \frac{-x^2}{a^2} + \frac{y^2}{b^2}$
+As always, set $z = k$, $\displaystyle \frac{-x^2}{ka^2} + \frac{y^2}{kb^2} = 1$.
+To rearrange this to get something easier to work with:
+$\displaystyle \frac{y^2}{kb^2} + \frac{x^2}{ka^2} \Rightarrow + y = \pm \frac{bx}{a}$
+So this is an asymptotic X'' graph, with hyperbolas. This happens in two
+planes, one with horizontal hyperbolas, and one with vertical. Next, let $x = k$,
+giving a vertically shifted parabola, opening upwards:
+$z = \frac{-k^2}{a^2} + \frac{y^2}{b^2}$
+and $y = k$, a downward facing, vertically shifted parabola:
+$z = \frac{-x^2}{a^2} + \frac{k^2}{b^2}$
+We can't be expected to visualize the saddle surface given this, but none the
+less we will need to do this on assignments.

\subsection*{Useful Inequalities}
\begin{itemize}
-\item $\|x + y\| \le \|x\| + \|y\|$
-\item $\|x - y\| \le \|x\| + \|y\|$
-\item $\|x\| - \|y\| \le \|x\| \pm \|y\|$
-\item $\|y\| - \|x\| \le \|x\| \pm \|y\|$
-\item $\|a\| < b \Rightarrow -b < a < b$
-\item $\|a\| < b \Rightarrow -b < a < b$
-\item $\|ab\| = \|a\| \cdot \|b\|$
-\item $\|\frac{a}{b}\| = \frac{\|a\|}{\|b\|}$
+\item $\mid x + y\mid \le \mid x\mid + \mid y\mid$
+\item $\mid x - y\mid \le \mid x\mid + \mid y\mid$
+\item $\mid x\mid - \mid y\mid \le \mid x\mid \pm \mid y\mid$
+\item $\mid y\mid - \mid x\mid \le \mid x\mid \pm \mid y\mid$
+\item $\mid a\mid < b \Rightarrow -b < a < b$
+\item $\mid a\mid < b \Rightarrow -b < a < b$
+\item $\mid ab\mid = \mid a\mid \cdot \mid b\mid$
+\item $\mid \frac{a}{b}\mid = \frac{\mid a\mid }{\mid b\mid }$
\item $a < b$ does not imply $a^2 < b^2$
\item Given $0 < x < 1$, if $x^p < x^q \Rightarrow p > q$
\end{itemize}
index 4e04e84..a8bd529 100644 (file)
@@ -8,6 +8,58 @@
\maketitle

\section*{Lecture 3 -- Limits}
-Limits in two variables.
+Limits in two variables. We have the standard definition from \emph{Calculus 1}
+To generalize to more variables, use the formular for Euclidean distance:
+$\| \vec{x} - \vec{x_0} \| = \sqrt{(x_1 - x_2)^2 + (y_1 - y_2)^2}$
+So using this in our limit definition:
+$\forall \epsilon > 0 \, \exists \delta > 0 \, \mathrm{such that} \, + \forall x, y \| \vec{x} - \vec{x_0} \| < \delta + \Rightarrow \mid f(\vec{x}) - L \mid < \epsilon \, \mathrm{and} \, + \vec{x} = (x,y), \vec{x_0} = (x_0, y_0)$
+If you picture this in 2D, we have a circular area around the points $\vec{x}$
+and $f(\vec{x})$ of radii $\epsilon$ and $\delta$, respectively. These are called
+the neighbourhoods of the points.
+
+When limits don't exist, there are three possible cases:
+\begin{itemize}
+\item Value goes to infinity ($\displaystyle \frac{1}{x}$ as $x \to 0$)
+\item Periodic functions (trigonometric functions)
+\item Two different limits from two sides (discontinuities)
+\end{itemize}
+
+Some simple examples in two variables:
+\paragraph*{Example 1}
+$\lim_{(x,y) \to (0,0)} \frac{1 + x^2y^6}{3 + x + x^3} = \frac{1}{3}$
+found by direct substitution
+
+\paragraph*{Example 2}
+$\lim_{(x,y) \to (0,0)} \frac{2 + x + y}{xy^3} = \infty$
+
+\paragraph*{Example 3}
+Cases with $\displaystyle \frac{0}{0}$ or $\displaystyle \frac{\infty}{\infty}$.
+$f(x,y) = \frac{x^2 - y^2}{x^2 + y^2}, + \lim_{(x,y) \to (0,0)}$
+We will prove by contradiction that this limit does not exist. Consider first
+the case were we get $\displaystyle \frac{0}{0}$. Fix $x = 0$ and let
+$y \to 0$, the limit of this is clearly $-1$. Conversely when we fix $y = 0$
+and let $x \to 0$ we get a limit of $1$ by l'H\^opital's Rule. Because these
+values are different, the limit does not exist.
+
+\paragraph*{Example 4}
+$f(x,y) = \frac{x^4y^4}{(x^4 + y^2)^3}, \, x,y \neq 0, +$
+When $x = 0$ we get a limit of $0$. Similarly for $y = 0$. So we can't find
+a contradiction yet. What if we approach $(0,0)$ from an arbirary line rather
+than one of the axes? Let $y = mx$ giving
+$\displaystyle \lim_{x \to 0} \frac{x^4(mx)^4}{(x^4 + (mx)^2)} + = \lim_{x \to 0} \frac{m^4x^2}{(x^2 + m^2)^3} = 0$. So we don't know
+any more information. We can find a contradition if try try letting $y = mx^2$,
+approaching $(0,0)$ from an arbitrary parabola. Solving that equation gives us
+$\displaystyle \frac{m^4}{(1 + m^2)^3} \neq 0$, which leads to a condradiction,
+hence the limit does not exist.
+
+So we can see that this approach isn't good for finding limits. It is also not
+incredibly useful for proving that limits exist as well. We need to figure out
+when to stop, and figure out strategies for different approaches to the problem.

\end{document}